1997
DOI: 10.1071/wf9970327
|View full text |Cite
|
Sign up to set email alerts
|

Seedling Mortality in Regeneration of Aleppo Pine Following Fire and Attack by the Scale Insect Matsucoccus josephi

Abstract: Mortality of Pinus halepensis seedlings was investigated in Israel during the first years of natural regeneration after fire, with special emphasis on the role of Matsucoccus josephi, drought and competition. The investigations were conducted in the native natural forest on Mt. Carmel, and in a plantation severely damaged by the scale insect at Horeshim in Samaria. M josephi was the dominant mortality agent during the first five years after regeneration, killing almost 73 % and 54% of the seedlings at Mt. Carm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Tree water stress resistance also increases with increasing tree size, accompanying greater fractional investment of plant biomass in roots in larger plants Tomlinson and Anderson, 1998). In fact, large trees can tolerate sustained drought periods extending over the entire growing season and even across multiple growing seasons , while such severe drought periods can lead to mortality of seedlings and saplings (for seedling physiological responses see Mendel et al, 1997;Mueller et al, 2005;Lopez and Kursar, 2007). The presence of large carbon reserves in mature plants can also allow for new shoot formation and resprouting (in resprouting species) following catastrophic events such as fire (Koskela, 2000;Langley et al, 2002) and breakage of branches or entire stem (Génard et al, 1998;Verdaguer and Ojeda, 2002;van Bloem et al, 2003;Wong et al, 2005;Vargas, 2009;Vargas et al, 2009).…”
Section: Effects Of Ontogeny On Stress Sensitivitymentioning
confidence: 99%
“…Tree water stress resistance also increases with increasing tree size, accompanying greater fractional investment of plant biomass in roots in larger plants Tomlinson and Anderson, 1998). In fact, large trees can tolerate sustained drought periods extending over the entire growing season and even across multiple growing seasons , while such severe drought periods can lead to mortality of seedlings and saplings (for seedling physiological responses see Mendel et al, 1997;Mueller et al, 2005;Lopez and Kursar, 2007). The presence of large carbon reserves in mature plants can also allow for new shoot formation and resprouting (in resprouting species) following catastrophic events such as fire (Koskela, 2000;Langley et al, 2002) and breakage of branches or entire stem (Génard et al, 1998;Verdaguer and Ojeda, 2002;van Bloem et al, 2003;Wong et al, 2005;Vargas, 2009;Vargas et al, 2009).…”
Section: Effects Of Ontogeny On Stress Sensitivitymentioning
confidence: 99%
“…In this sense, several studies carried out in the Mediterranean Basin have shown that P. halepensis seedlings and saplings increase growth if both intra-and interspecific competition are reduced [27,29]. Scrubbing, which is focused on the seedlings survival [7] is another silviculture treatment carried out in early stages of pine stands (no more than 2 years old).…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of higher mortality of smaller trees in CM was consistent with the recent die off event of Pinus edulis between 2002 and 2004 Arizona, New Mexico, Colorado, and Utah, although Mueller et al (2005) observed the opposite pattern during the 1996 and 2002 acute droughts in piñon-juniper woodlands of northern Arizona. My results in the CM were consistent with the trend of high seedling and sapling mortality under drought relative to larger trees that, with their deeper root systems and larger carbon stores, were able to survive those same drought events (Mendel et al, 1997;Mueller et al, 2005;Lopez andKursar, 2007, Ganey andVojta 2011). The lack of evidence of bark beetle infestation in trees that died over the sampling interval also suggests that the high mortality of small-diameter trees was not related to insect attack.…”
Section: Preferential Mortality Of Small Treessupporting
confidence: 71%